A Novel QWT Fed Penta- Band Microstrip Patch Antenna for Various Wireless Applications - Dr. R. Gayathri Rajaraman (Journal of Electronic Design Engineering, 2017)
A conventional patch antenna is initially designed with edge fed feeding. The four edges of patch are chamfered to make it octagon shaped. Further four slots two in horizontal and two oriented vertically are etched on the patch. A H shaped Slot is created on Ground. The result is a multi- resonant antenna for SATCOM and RADAR applications. The use of flexible substrate is to suit the chosen wireless applications. The optimized antenna model with its vital parameters are presented in this paper.